Think Twice before Prescribing Antibiotics for That Swollen Knee: The Influence of Antibiotics on the Diagnosis of Periprosthetic Joint Infection - Graham S. Goh; Javad Parvizi (MDPI AG, 2021)
Periprosthetic joint infection (PJI) is a rare but devastating complication after total joint arthroplasty. An estimated 7-12% of patients have negative cultures despite clear clinical evidence of infection. One oft-cited reason for this occurrence is the administration of antibiotics in the weeks prior to obtaining cultures. This article reviews the influence of antibiotics on the diagnosis of PJI. Specifically, we examine the effect of prophylactic and therapeutic antibiotic administration on the diagnostic accuracy of microbiological cultures as well as serum and synovial biomarkers. We also explore the potential of molecular techniques in overcoming these limitations in patients who have received antibiotics before specimen collection and propose areas for future research.